Analysis of Implementation of Ferrous Tablets Supplementation Program for Adolescent Girl ini Bukittinggi - Mesalina, Rosa; Dariani, Lili; Rahmai, Sania Lailatu (Universitas Andalas, 2024)
Anemia has become one of the nutritional problems in the world. The government has made efforts to prevent anemia through the provision of iron supplement tablets, but its implementation has not been optimal in reducing the incidence of anemia. The purpose of the research is to analyze the iron tablet supplementation program for adolescents in Bukittinggi. The research is qualitative with a phenomenological study approach. The sample was determined through purposive sampling, consisting of 11 people. Data were collected through in-depth interviews and focus group discussions using interview guideline research instruments. Data were analyzed using thematic analysis as a construction for developing an intervention model for anemia prevention efforts. The research findings identified important themes, namely the unavailability of regional regulatory policies, limited human resources, funding, utilization of promotional media, weak monitoring and evaluation systems, suboptimal recording and reporting, as well as obstacles from cultural factors, low knowledge, lack of concern, and suboptimal family support. It is recommended to initiate a regional policy study to accommodate the solutions found in the research.